Microstructures of a pressure die cast Al-8.5%Si-3.5%Cu alloy - Barbés Fernández, Miguel Ángel; Quintana, María José; Verdeja González, José Ignacio; Gonzalez-Ojeda, Roberto (My University, 2017)
Quantitative microstructural measurements of constituents of an Al-Si-Cu alloy, used to manufacture a part with thin sections by Pressure Die Casting (PDC), do not correspond to phase diagram calculations. A simulation of the liquid velocity when filling the mold was made in order to understand the relation between this parameter and pressure, cooling rate and the eutectic amount and morphology. Also, the microstructures of the same alloy solidified in a ceramic crucible (low cooling rate) and in a metal flask (high cooling rate) were compared to those obtained by PDC to analyze the role of pressure on the displacement of eutectic composition and formation of different eutectic morphologies. The amount of constituents varies with distance from the mold walls, producing higher or lower pressure zones, which may be estimated from the Al-Si phase diagram simulation at different pressures. As these pressures must be very high (∼ 2 GPa), a possible explanation for the displacement of the eutectic point is the combination of high cooling rate of the manufacturing process, entrapment of gases during solidification and influence of the alloying elements.